Effect of Concentration and Application Interval of Chlorantraniliprole Active Ingredient Insecticide on Attack Intensity of Spodoptera frugiperda J.E Smith (Lepidoptera: Noctuidae) and Yield of Sweet Corn (Zea mays saccaharata sturt) Plants - Subagja, Rizki Ahmad; Agustiani, Tanty; Hidayati, Laili Nur; Yudi, Jefri; Deden, Deden; Dukat, Dukat (Green Publisher Indonesia, 2023)
Sweet corn productivity in the country is still low when compared to productivity abroad, the main factors that cause low corn yields in Indonesia are the use of local varieties, lack of soil fertility coupled with inadequate fertilization and pest and disease attacks. This experiment aims to determine the effect of Concentration and Application Interval of Chlorantraniliprole Active Ingredient Insecticide on the intensity of Spodoptera frugiperda J.E Smith (Lepidoptera: Noctuidae) attack and yield of Sweet Corn (Zea mays saccaharata sturt). The experiment was conducted in Getasan Village, Depok District, Cirebon Regency, in January-April 2023. The research method used a factorial pattern Randomized Group Design consisting of two factors, namely concentration and application interval. The results showed that the concentration and application interval of the active ingredient Chlorantraniliprole had a significant effect on the intensity of Spodoptera frugiperda attack and the yield of sweet corn (Zea mays saccaharata sturt). Chlorantraniliprole concentration of 3 cc/liter with 2 application intervals once a day was able to reduce the intensity of Spodoptera frugiperda attack up to 9.47%. Chlorantraniliprole concentration of 2 cc/liter with 2 application intervals once was able to produce 10.8 kg/plot of corn or equivalent to 19.2 ton/h (80% effective land).